Tessituras da formação em avaliação educacional: os desafios à cultura de avaliação e a busca por uma educação crítico-reflexiva - Carvalho, Wirla Risany Lima (2016)
Before the context of complexity, presented at the XXI century, and was called the Knowledge Society, Education, greatly, is impacted the most structural concepts of their training. The educational evaluation suffers the effects of a scenario that requires strong knowledge and applicability for the development of effective educational practices. This research aimed to diagnose how the relationship between scientific and spontaneous knowledge is presented as an important factor for internalizing the concept of educational evaluation by the teacher and for a reconstruction proposal in teacher training in evaluation culture. Specifically, purposed: i) investigate whether the reproduction of evaluation as test culture is a recurring practice in teacher evaluation practice, when there is no scientific knowledge to promote the teacher a process of internalization of the concept of evaluation of teaching and learning based on a culture evaluation; ii) establish whether scientific knowledge is of fundamental importance for the teacher in the process of formation of the concept of assessment of teaching and learning in search of a practical evaluation culture and critical-reflexive education; iii) seek theoretical support that could support the implementation of a mandatory training in educational evaluation during training in pedagogy and other degrees in HEIs, as a fundamental fact for the exercise of a teaching practice in evaluation culture. The backbone of the study was the formation of theory concepts of Vygotsky, complemented by expertise in the area of teacher training and educational evaluation. The research approach was qualitative-quantitative, applied nature, using the qualitative aspects of hermeneutic phenomenology of Heidegger and Gadamer; and the quantitative factor analysis and the chi-square test. Data from the quantitative sample was collected with 500 teachers working in public schools in the city of Fortaleza, Ceará, through Likert scales, then with intentionally small number of participants of the expanded sample, be the application of semi-structured interviews for membership spontaneous. the SPSS 20.0 and Atlas t.i7 for analysis of qualiquantitativos data were used. The applied research answered the study questions and diagnosed that the relationship between scientific and spontaneous knowledge is presented as an important factor in the internalization of the concept of assessment by the teacher and for a reconstruction proposal in teacher training in evaluation culture because, it was on the realization of this intrinsic relationship that teachers have proved in their formative and conceptual weaknesses in the evaluation field. It has been found that the reproduction of evaluation as test culture is a recurring practice in teacher evaluation practice, when there is no scientific knowledge to promote the teacher a process of internalization of the concept of evaluation of teaching and learning based on an evaluation culture. It was also found that scientific knowledge is of fundamental importance for the teacher in the process of formation of the concept of assessment of teaching and learning in search of a practical evaluation culture and critical-reflexive education. Finally, presented are many theoretical support - in the form of search results - that support the implementation of a mandatory training in educational evaluation during training in pedagogy and other degrees in HEIs, as a fundamental fact for the exercise of teaching practice in evaluation culture. It can be assumed that even in other courses of IES, particularly those who require the evaluation of teaching and learning as a fundamental fact for the exercise of a teaching practice in evaluation culture. It has been argued in this study the thesis that if there are serious deficiencies in teacher training in educational evaluation - for a teaching practice in evaluation of teaching and learning to run under the aegis of the evaluation culture and a critical-reflexive education - there is a pressing need for mandatory scientific training in educational evaluation during initial training in pedagogy courses and degrees of higher education institutions (HEIs). It is expected that the impact on higher education is promoting the generation of a class of teaching teachers-scientists produce knowledge, not only teachers-teachers who reproduce and pass a knowledge produced elsewhere in relation to educational evaluation. These professors-researchers can make the classroom a research space where promote social change, from her students, awakening these to their own identity and quest for autonomy as a citizen, as a person who was educated critical and reflexively for thinking and act within a libertarian view.